2015
DOI: 10.1017/jns.2015.5
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of Bifidobacterium breve B-3 modifies metabolic functions in adults with obese tendencies in a randomised controlled trial

Abstract: Accumulating evidence suggests an association between gut microbiota and the development of obesity, raising the possibility of probiotic administration as a therapeutic approach. Bifidobacterium breve B-3 was found to exhibit an anti-obesity effect on high-fat diet-induced obesity mice. In the present study, a randomised, double-blind, placebo-controlled trial was conducted to evaluate the effect of the consumption of B. breve B-3 on body compositions and blood parameters in adults with a tendency for obesity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
81
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 48 publications
4
81
2
Order By: Relevance
“…In contrast, there are few clinical studies evaluating the efficacy of probiotic bifidobacteria on visceral fat in humans. Minami et al reported that consumption of B. breve B-3 reduced fat mass measured by a bioelectrical impedance method in adults but did not reveal a change in visceral adipose tissue [33]. In the present study, we clearly demonstrated the utility of probiotic bifidobacteria to reduce visceral fat in humans, as in previous animal studies [30,31,32].…”
Section: Discussionsupporting
confidence: 86%
“…In contrast, there are few clinical studies evaluating the efficacy of probiotic bifidobacteria on visceral fat in humans. Minami et al reported that consumption of B. breve B-3 reduced fat mass measured by a bioelectrical impedance method in adults but did not reveal a change in visceral adipose tissue [33]. In the present study, we clearly demonstrated the utility of probiotic bifidobacteria to reduce visceral fat in humans, as in previous animal studies [30,31,32].…”
Section: Discussionsupporting
confidence: 86%
“…Four clinical studies involving healthy, overweight and/or obese participants have investigated the effects of micro-organisms on weight management or body fat mass (Kadooka et al, 2010, Kadooka et al, 2013, Minami et al, 2015, Sanchez et al, 2014). The effect size seen in the current study (6.7% difference in trunk fat between LU + B420 and Placebo) is quite comparable to that seen in 12-week interventions with Lactobacillus gasseri SBT2055 where abdominal fat was reduced by approximately 4.5% compared to placebo (Kadooka et al, 2010, Kadooka et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to compare the employed statistical methodology, however, because it remains unclear which participants were included in the analyses. In comparison, intake of Bifidobacterium breve B-3 reduced body fat mass by 0.6 kg compared to placebo within 12 weeks (Minami et al, 2015). It should also be noted that the study participants in these three studies were Japanese whereas the present study was conducted on a Western population.…”
Section: Discussionmentioning
confidence: 99%
“…lactis CNCM I-2494Vegetable and dairy productsEach strain selectively altered a specific subset of key bacteria species that were significantly associated with MS.[15]Partially reversed HFD-induced structural changes in the gut microbiota Significant reduction in TNF-α expression in HFD-fed mice. Bifidobacterium breve B-3Healthy infantSignificantly lowering fat mass in human subjects. Improvements in some blood parameters related to liver function and inflammation.[30] Lactobacillus gasseri SBT2055Fecal specimen of a healthy adultLG2055 dose-dependently suppressed lipase activity in the fat emulsion assay. LG2055 dose-dependently increased fat emulsion droplet size.[31] Lactobacillus rhamnosus GG Lactobacillus paracasei TMC0409 Significant reduction in weight, fat accumulation and adipocyte fatty acid synthase (FAS) activity.…”
Section: Probiotic Lab and Obesity Treatmentmentioning
confidence: 99%